Phytochrome-dependent temperature perception modulates isoprenoid metabolism - Bianchetti, Ricardo; De Luca, Belen; De Haro, Luis Alejandro; Rosado, Daniele; Demarco, Diego; Conte, Mariana; Bermudez Salazar, Luisa; Freschi, Luciano; Fernie, Alisdair R.; Michaelson, Louise V.; Haslam, Richard P.; Rossi, Magdalena; et al. (American Society of Plant Biologists, 2022)
Changes in environmental temperature influence many aspects of plant metabolism; however, the underlying regulatory mechanisms remain poorly understood. In addition to their role in light perception, phytochromes (PHYs) have been recently recognized as temperature sensors affecting plant growth. In particular, in Arabidopsis (Arabidopsis thaliana), high temperature reversibly inactivates PHYB, reducing photomorphogenesis-dependent responses. Here, we show the role of phytochrome-dependent temperature perception in modulating the accumulation of isoprenoid-derived compounds in tomato (Solanum lycopersicum) leaves and fruits. The growth of tomato plants under contrasting temperature regimes revealed that high temperatures resulted in coordinated up-regulation of chlorophyll catabolic genes, impairment of chloroplast biogenesis, and reduction of carotenoid synthesis in leaves in a PHYB1B2-dependent manner. Furthermore, by assessing a triple phyAB1B2 mutant and fruit-specific PHYA- or PHYB2-silenced plants, we demonstrated that biosynthesis of the major tomato fruit carotenoid, lycopene, is sensitive to fruit-localized PHY-dependent temperature perception. The collected data provide compelling evidence concerning the impact of PHY-mediated temperature perception on plastid metabolism in both leaves and fruit, specifically on the accumulation of isoprenoid-derived compounds.